UNDERGRADUATE STUDENTS’ PERSPECTIVE ON THE IMPLEMENTATION OF HYBRID LEARNING IN SEMINAR ON ELT COURSE AT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Kahar, Mutmainnah Mutia; abdullah, Nurdevi Bte; Rum, Eka Prabawati (Journal of Computer Interaction in Education, 2024)
This research used a qualitative approach to know students' perspectives on the implementation of hybrid learning models in the subject of seminars on ELT at Muhammadiyah University of Makassar. The research subjects were BGE19 class students totaling 10 people. Data collection was carried out by conducting interviews and presented in descriptive form.The results of this study show 3 different views in several aspects. Some students have positive, neutral, and negative perspectives on the implementation of hybrid learning models on the subject of seminars on ELT at Muhammadiyah University of Makassar. But most students have a positive perspective stating that this hybrid learning model is favored and expected to be applied to other subjects. It can be concluded that the implementation of hybrid learning models on the subject of seminars is preferred and expected by students. The hybrid learning model should be improved and applied to other subjects by utilizing increasingly adequate technology to make the learning process more effective.